Research as a Path for the Constant Updating of Knowledge - Cardozo Rincón, Gerardo (Rastros Rostros, 2014)
This article presents certain aspects of research in the academic setting. First, it puts forward the impossibility of objectivity being a challenge that researchers must meet; here it is shown as a factor that increases researchers’ commitment. Following this, the roles of those who are involved in academic research are highlighted. The part played by the tutor is examined, and mention is made of some options available to judges when looking at the research work of students presenting their theses. The final part of this article offers some examples of what can occur in the evaluation of final research reports.
Keywords: updating of knowledge; research; objectivity; paradigms